Spanish Cross-Cultural Adaptation and Validation of Neck Bournemouth Questionnaire (NBQ) for Neck Pain Patients. - Pérez-García, Juan José; Molina-Torres, Guadalupe; Ventura-Miranda, María Isabel; Sandoval-Hernández, Irene; Ruiz-Fernández, María Dolores; Martínez-Cal, Jesús; González-Sánchez, Manuel (MDPI, 2023)
Background: Neck pain is highly prevalent and one of the most common musculoskeletal conditions. Instruments that measure the factors involved in neck pain accurately are needed for clinical assessment. Patient-reported outcome measures (PROMs) are reliable, cost-effective, and specific tools for the assessment of musculoskeletal problems at different moments. The Neck Bournemouth Questionnaire (NBQ) assesses pain, function, disability, and psychological and social variables in patients with cervical pathologies. The aim of this study was to perform an adaptation and validation into Spanish of the NBQ (NBQ-Sp). Methods: A cross-sectional, observational study was carried out through translation, adaptation, and validation. A total of 129 patients with neck pain, of Spanish nationality, and over 18 years of age were included. Results: The NBQ-Sp showed excellent internal consistency, with Cronbach’s of 0.897, test–retest reliability with interclass correlation coefficient (ICC) of 0.866, and standard error of measurement (SEM) and minimum detectable change (MDC) values were 1.302 and 3.038, respectively. A Kaiser–Meyer–Olkin value of 0.857 was obtained, and Bartlett’s test yielded p < 0.001, finding one factor in the factor analysis. Conclusion: The NBQ-Sp has proven to be a valid and reliable tool for clinicians and researchers to measure neck pain in the Spanish population.
Keywords: Cervicalgia - Diagnóstico; Cross-cultural adaptation; Questionnaires; Neck pain; Neck Bournemouth Questionnaire; Surveys; Validation